Pengaruh Annealing Pada Perubahan Sifat Mekanis dan Sifat Fisis Pada Pengelasaan Baja Untuk Chasis Mobil - Widodo, Tri, Pramuko IP,Ir.MT (2016)
Carbon steel is a metall alloy that formed by Fe as a main element and carbon that impact to the caracteristic, where as other elements are present in quantities to affect its properties. Based on their role,steel grouped into tw categories: construction steel and tool steel. Construction steel has a carbon content between 0.06% to 0.55%, while the tool steel has a carbon content between 0.50% to 2.06%. This study begins with the cutting of specimens followed by SMAW welding methods. The process uses a powerful current of 100 A, 105 A and 110 A. After that proceed with the establishment of the specimens in accordance with ASTM test standard E8 then pull with treatments in 8500C. The results of micro photo showed that the specimen in treatments are enlarged on ferrite. While in material hardness testing on welded test specimens with welding without visible THAT treatments weld metal regions have a higher hardness than the HAZ and base metal regions. This happens because the metal area weld thermal cycle greatest at the time of welding. While the tensile test specimens that undergo heat treatment received by an object will alter the microstructure of these objects, where the object constituent grain structure will be changed and the maximum voltage decreases. Keywords: low carbon steel, treatment, tensile testing, Vikers, micro photo